Arrhenius Plot Analysis of the Temperature Effect on the Biodegradation Rate of 2-chloro-4-nitrophenol - Mohd Yunus Shukor (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2020)
Several models are available to determine the effect of temperature on the growth rate of microorganisms on substrates. An example is Arrhenius model, which is very popular because it has few parameters. For the first time, a discontinuous chevron-like graph of apparent activation energy based on the Arrhenius plot on the growth of 2-chloro-4-nitrophenol by Cupriavidus sp. is reported. The plot of ln mm against 1/T shows a discontinuous chevron-like graph for the entire investigated temperature range with an inflection at 27.75°C. This indicates that the existence of 2 activation energies for growth on 2-chloro-4-nitrophenol ranges from 20 to 40°C. Furthermore, a regression analysis from 20–25°C and 30–40°C results in activation energies of 88.71 kJmol-1 and 75.16kJ mol-1, respectively. This is probably the first time a Chevron-like graph was observed for the Arrhenius plot on the effect of temperature on the growth rate of 2-chloro-4-nitrophenol.